2015
DOI: 10.1002/app.42134
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic control in conductive PP/PMMA/EAA carbon black composites

Abstract: Multiphase polymer blends provide unique morphologies to reduce the percolation concentration and increase conductivity of carbon-based polymer composites via selective distribution of the conductive filler. In this work, the kinetic and thermodynamic effects on a series of multiphase conductive polymer composites were investigated. The electrical conductivity of carbon black (CB)-filled conductive polymer blend composites comprising polypropylene, poly(methyl methacrylate), and ethylene-acrylic acid were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…The overall increase in conductivity of the PP/PMMA/(EAA‐CB) system compared to the single‐phase system in Figure is not due to the percolation of the CB, but is believed to be due to changes in the phase morphology and the formation of a completely connective EAA‐CB network. Previous experimental work showed that the morphology and resultant conductivity was found to be kinetically driven during the intensive compounding process and transitioned from kinetic to thermodynamic control after long annealing times . However in addition, we have found in a separate study that beyond a critical loading of conductive filler particles in the minor EAA phase, especially for high aspect ratio fillers such as the type of CB used in this work, phase separation is slowed significantly due to the aggregation of particles into a network formation within the EAA phase causing a significant increase in phase viscosity which can impact the overall morphology development.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The overall increase in conductivity of the PP/PMMA/(EAA‐CB) system compared to the single‐phase system in Figure is not due to the percolation of the CB, but is believed to be due to changes in the phase morphology and the formation of a completely connective EAA‐CB network. Previous experimental work showed that the morphology and resultant conductivity was found to be kinetically driven during the intensive compounding process and transitioned from kinetic to thermodynamic control after long annealing times . However in addition, we have found in a separate study that beyond a critical loading of conductive filler particles in the minor EAA phase, especially for high aspect ratio fillers such as the type of CB used in this work, phase separation is slowed significantly due to the aggregation of particles into a network formation within the EAA phase causing a significant increase in phase viscosity which can impact the overall morphology development.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 68%
“…Previous experimental work showed that the morphology and resultant conductivity was found to be kinetically driven during the intensive compounding process and transitioned from kinetic to thermodynamic control after long annealing times. 22 However in addition, we have found in a separate study that beyond a critical loading of conductive filler particles in the minor EAA phase, especially for high aspect ratio fillers such as the type of CB used in this work, phase separation is slowed significantly due to the aggregation of particles into a network formation within the EAA phase causing a significant increase in phase viscosity which can impact the overall morphology development. Chen et al 42 reported similar behavior in a PP/PMMA binary system where the coarsening process of the composites was significantly suppressed with the incorporation of carbon nanotubes.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…A suitable third polymer must fulfill two conditions: [27][28][29] (1) it must thermodynamically form the interphase of a tricontinuous blend, and (2) it must have the highest affinity for conductive particles among the three polymer components. For example, the addition of a styrene-butadiene-styrene triblock copolymer and an ethylene-acrylic acid copolymer can drive CB particles to the interfaces of polypropylene (PP)-polystyrene and poly (methyl methacrylate)-PP blends, 27,28,[30][31][32][33][34] respectively, and the precompounding of carbon nanotubes with maleic anhydride grafted acrylonitrile-butadiene-styrene and pyridine-modified poly(ethylene-co-methacrylic acid) can drive the carbon nanotubes to the interfaces of polycarbonate-acrylonitrile-butadiene-styrene and polyamide 12-PP blends, 29,35 respectively. So far, all of the studies on conductive particle-filled ternary polymer blends have dealt with driving conductive particles to the interface of the two major phases by the interfacial localization of the minor, third polymer component.…”
Section: Introductionmentioning
confidence: 99%